Disruption of evasive immune cell microenvironment in tumors reflects immunity induced by radiation therapy - Filatenkov, Alexander (Oncoimmunology, 2016)
Radiation administered to murine colon tumors induced durable remissions that were dependent on CD4(+) and CD8(+) T cell immunity, and antigen cross priming CD8(+) dendritic cells (DCs). Remissions were associated with marked reductions in the infiltration of myeloid-derived suppressor cells (MDSCs), tumor-associated macrophages (TAMs) and Treg cells, and a marked increase in CD8(+) T cells.